Wages and nominal and real unit labour cost differentials in EMU - Horn, Gustav A.; Watt, Andrew (Luxembourg, 2017)
"This paper addresses the issue of current account imbalances of countries within a monetary union, now widely agreed to have been a major contributor to the persistent economic crisis in the EMU. In particular we focus on the role of wages for current account developments and a possible role for nominal incomes policies in limiting and correcting imbalances. We set out why national current accounts remain important in a monetary union and examine the forces driving the current account balance. We present empirical evidence on current account developments in the Euro Area, focusing on countries in which a correction has occurred. Detailed counter-factual model-based simulations for Germany show that “wage policy” on its own is scarcely able to make an impact on its huge and destabilising surplus; what is needed is a combined approach in which nominal wages follow a wage norm (productivity plus ECB target inflation rate) while aggregate demand is managed (in this case stimulated) to fully utilise productive potential. Against this analytical background we develop a proposal for institutional reform of the Euro Area, building on existing institutions. Key elements are: reinstating the Broad Economic Policy Guidelines as the conceptual framework guiding economic policy, expanding the remit of the Fiscal Council and the Productivity Boards to cover the entire policy mix, and substantially developing the EU Macroeconomic Dialogue in particular by setting up MEDs at Euro Area and Member State levels."